The Role of Young Coconut Water as a Rehydration Beverage on Hydration Status and Work-Related Fatigue - Amiluddin, Laode Asaid Alriza; Mulasari, Surahma Astri; Suryani, Dyah (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
Dehydration is a common problem among individuals engaged in physical activity and workers exposed to heat, and it contributes to decreased work capacity and increased fatigue. Effective rehydration strategies require not only adequate fluid intake but also sufficient electrolyte replacement to maintain body fluid balance. Young coconut water is a natural beverage rich in electrolytes and has the potential to serve as an alternative rehydration drink. This study aimed to systematically synthesize empirical evidence regarding the role of young coconut water as a rehydration beverage on hydration status and work-related fatigue. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Literature searches were performed using three electronic databases Google Scholar, ScienceDirect, and MDPI and resulted in 16 articles that met the inclusion criteria. The synthesis results indicate that young coconut water consumption consistently contributes to the maintenance of hydration status, reduces work-related and physical fatigue, and supports physiological recovery following physical activity. However, its effects on physical performance were found to be variable and context-dependent. Overall, young coconut water demonstrates potential as a natural rehydration strategy, particularly in the context of physical activity and heat-exposed working environments.